Nutrient composition of rations for short-term, high-intensity combat operations (National Academies Press, 2006)
Recognizing the importance of good nutrition for physical and mental status, the Department of Defense asked the Institute of Medicine to guide the design of the nutritional composition of a ration for soldiers on short-term, high-stress missions. This book considers military performance, health concerns, food intake, and food technology issues.